COSMIC RAYS AND THE MAGNETIC FIELD OF THE MOON - SANDOVAL VALLARTA, MANUEL (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO, INSTITUTO DE FISICA, CD. MEXICO, DF, MEX, 1962)
It is therefore clear that the present difficulties4 concerning the origin of the diurnal and seasonal variations of the intensity of cosmic radiation cannot be traced to a possible magnetic field of the moon of the magnitude predicted by Blackett's theor
PHYS REV
Keywords: COSMIC RAYS, MAGNETIC FIELD, MOON; MULTIDISCIPLINARIA; ELECTROMAGNETISMO; MAGNETISMO